2015
DOI: 10.1016/j.drugalcdep.2015.09.012
|View full text |Cite
|
Sign up to set email alerts
|

The importance of stress, self-efficacy, and self-medication for pharmacological neuroenhancement among employees and students

Abstract: Objectives: This study examined the relationship between stress, self-efficacy, self-medication, and pharmacological neuroenhancement (PNE) in the Swiss general population. Methods: Using the largest Swiss Internet panel, a sample of 10,171 employees and students (unweighted N = 10,084) aged 15 to 74 years was recruited and asked to complete a self-administered online survey. The data were weighted for age, sex, and language region to provide results that were representative of the Swiss population. Multinomia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
29
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 34 publications
5
29
1
4
Order By: Relevance
“…This finding resembles several prior studies on different substances specific or unspecific to CE (Brown et al, ; Lazuras et al, ; Maier, Haug, & Schaub, ; Middendorff et al, ; Peck et al, ; Schröder et al, ; Wolff & Brand, ). However, some studies found no effects of different indicators for stress (Lazuras et al, ; Maier, Haug, & Schaub, ). The finding of this study could be understood from different theoretical perspectives (e.g., self‐medication hypothesis, stress coping, strain theory, and the job demands–resources theory).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…This finding resembles several prior studies on different substances specific or unspecific to CE (Brown et al, ; Lazuras et al, ; Maier, Haug, & Schaub, ; Middendorff et al, ; Peck et al, ; Schröder et al, ; Wolff & Brand, ). However, some studies found no effects of different indicators for stress (Lazuras et al, ; Maier, Haug, & Schaub, ). The finding of this study could be understood from different theoretical perspectives (e.g., self‐medication hypothesis, stress coping, strain theory, and the job demands–resources theory).…”
Section: Discussionsupporting
confidence: 90%
“…Findings on age are also mixed. Several studies found a higher likelihood of prescription drug use (including for CE) in younger populations (Maier, Haug, & Schaub, ; Novak et al, ; Schröder et al, ). Few studies found the opposite (Singh et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations